The Influence of Average Collection Periods on Cash Ratio, Net Profit Margin, and Return on Assets at PT Angkasa Pura I Persero Branch of I Gusti Ngurah Rai International - R Ristanti; I N Sugiarta; I M Ariana (Jurusan Akuntansi Politeknik Negeri Bali, 2019)
Account receivable has a very important role in the company. Account receivable arising from the occurrence of credit sale transaction. Account receivable is able to boost profits once a certain risk. For a company that claimed to be more careful in managing their receivable in both the delivery and billing. This research was conducted at PT Angkasa Pura I (Persero) Branch of I Gusti Ngurah Rai International Airport – Bali. The purpose of this study is to know the influence of average collection periods to cash ratio, net profit margin, and return on assets. Type of data used in research is secondary data from period 2005 – 2017 financial statement. Data analysis methods used in this study is the method of simple linier regression analysis at a significance level of ἀ=5%. This linier test is using IBM SPSS version 23.The result showed that average collection periods has significant effect on the cash ratio because the significance value is less than 0.05 (0.00<0.05) and average collection periods also has significant effect on the net profit margin because the significance value is less than 0.05 (0.003<0.05). Instead, average collection periods has no significant effect on return on assets because significance value is more than 0.05(0.062>0.05).